The Agency-Governance-Disruptions Model for Operational Efficiency, Profitability and Value Delivery: An Application to Private and Public Enterprises in Nigeria - Awodun, Muritala; Adam, Lukman (Archives of Business Research, 2025)
In relating the agency theory to corporate governance and technological disruptions in organizations, this paper examines this tripod through the creation of an agency-governance-disruptions model. The paper relates the model to operational efficiency, profitability and value delivery in selected private and public enterprises in Nigeria. The outcome reveals that the tripod of agency-governance-disruptions, as presented through the model, significantly impacts on operational efficiency, profitability and value delivery of organizations in Nigeria. This is based on applying the model to selected private and public universities in Nigeria, with the findings revealing that the agency-governance-disruptions model has a very significant impact on the efficiency, revenue generation/profitability and value delivery of the private universities, while for public universities, on the other hand, the effects are not so significant.